Relationship between authentic leadership and job satisfaction among undergraduate nursing professors - Cezar Augusto da Silva Flores; André Almeida de Moura; José Luis Guedes dos Santos; Alexandre Pazetto Balsanelli; Carmen Silvia Gabriel; Andrea Bernardes (Revista Latino-Americana de Enfermagem)
Objective: to analyze the relationship between the exercise of authentic leadership by coordinators and job satisfaction among professors of undergraduate nursing courses at federal public universities. Method: this is a quantitative study with an observational, analytical, and cross-sectional design. Twelve undergraduate nursing courses at public higher education institutions were chosen to participate in the study. The information collected was analyzed using descriptive statistical techniques, Spearman’s correlation test, and binary logistic regression analysis, with a 5% significance level. Results: the sample consisted of 179 professors who completed the Sociodemographic Questionnaire, the Authentic Leadership Questionnaire, and the Job Satisfaction Questionnaire. The professors rated the course coordinators as having high levels of authentic leadership practice. As for the binary logistic regression, only the Relational and Moral domain showed significance (p-value < 0.0001), indicating that when this domain is present, there is a 5.48-fold increase in the chance of professors being satisfied. Conclusion: the results of the study indicate that the job satisfaction of professors in undergraduate nursing courses is influenced by the practice of authentic leadership on the part of the coordinators.